2022
DOI: 10.4103/jpbs.jpbs_713_21
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pattern of Mandibular Fractures

Abstract: Objective: The main objective of this study is to analyze the prevalence of age, gender distribution, etiology, anatomic distribution, and treatment of mandibular fractures. Materials and Methods: This 2-year retrospective study was carried out in few multispeciality hospitals in India. The results were collected, and descriptive statistics were analyzed using SPSS. Results: Of 180 patients that were analyzed, males and the age group of 20–30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
(8 reference statements)
0
0
0
Order By: Relevance
“…Saravanan et al, 7 in their study reported that males constituted up to 88% of the patients. Similar findings were reported by Saluja et al 8 (2022) and Farzan et al 9 ( 2021).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Saravanan et al, 7 in their study reported that males constituted up to 88% of the patients. Similar findings were reported by Saluja et al 8 (2022) and Farzan et al 9 ( 2021).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, 97 patients (91.5%) out of 106 patients had RTA as the mechanism of injury followed by assault (4.7%) and fall (3.8%). Similar findings were reported by Shah et al, 10 Saluja et al 8 (2022) and Tabatabaee et al 11 Lapeña et al, 12 advocated road safety measures such as proper use of helmets to prevent mandible fractures.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…3 Symphysis/parasymphysis fractures of the mandible have been reported to occur in 9% to 57% of cases. [4][5][6] The treatment of parasymphysis fractures is the same as other mandible or maxillofacial fractures introduced by Hippocrates in 460-375 BC. It uses occlusion guidelines or the ideal relationship between the lower teeth and maxillary teeth.…”
Section: Introductionmentioning
confidence: 99%